If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7xy + -3x + y) + -1(2x + -1y + 6xy) = 0 Reorder the terms: (-3x + 7xy + y) + -1(2x + -1y + 6xy) = 0 Remove parenthesis around (-3x + 7xy + y) -3x + 7xy + y + -1(2x + -1y + 6xy) = 0 Reorder the terms: -3x + 7xy + y + -1(2x + 6xy + -1y) = 0 -3x + 7xy + y + (2x * -1 + 6xy * -1 + -1y * -1) = 0 -3x + 7xy + y + (-2x + -6xy + 1y) = 0 Reorder the terms: -3x + -2x + 7xy + -6xy + y + 1y = 0 Combine like terms: -3x + -2x = -5x -5x + 7xy + -6xy + y + 1y = 0 Combine like terms: 7xy + -6xy = 1xy -5x + 1xy + y + 1y = 0 Combine like terms: y + 1y = 2y -5x + 1xy + 2y = 0 Solving -5x + 1xy + 2y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. -5x + 1xy + 2y + -2y = 0 + -2y Combine like terms: 2y + -2y = 0 -5x + 1xy + 0 = 0 + -2y -5x + 1xy = 0 + -2y Remove the zero: -5x + 1xy = -2y Combine like terms: -2y + 2y = 0 -5x + 1xy + 2y = 0 The solution to this equation could not be determined.
| 7x^2=-9 | | (x+y)*dy+(3x+3y-4)*dx=0 | | X/20=0.9 | | 7(9x--8)=6244 | | 6x-4=8x+9 | | 5(x-5)=41-6x | | 3x+4=1-x | | x+29+80=180 | | 4x-8=69-7x | | 6x+3=6+3x | | 9=-4(2t-7) | | 8y+17=1-7 | | 3y+7=2y+1 | | (10x+4)+(15x+1)=180 | | (2x+3)+(3x+12)=90 | | 11x-1=5x+8 | | (3x+12)+(2x+3)=180 | | 3x+3y=18023 | | (3x)^5/)(3x)^5 | | (x-2)(x-3)(x-7)=0 | | (7-3f)/4=2 | | x+(x*0.1)=33.33 | | 5x+5=59-4x | | 50y-4-y=12+15y-1 | | 4x+9=30-20x-10+2x | | -(c-9)=-173 | | 2x+z=2a+b | | 101+3z=1-17z | | 5(3s+10)=95 | | 70-4y=10-7y | | 6(2l+8)=180 | | 2a+b-2x=z |